Association Between Glomerular Filtration Rate And Body Mass Index Among Orthopaedic Patients In Kano-Nigeria - SM, Adamu; AM, Wudil; MK, Atiku; AJ, Alhassan; A, Ibrahim; MN, Salihu; YA, Koki; S, Adamu (European Scientific Journal, ESJ, 2016)
Any association between body mass index and kidney disease has so far proved inconclusive. Therefore, this study is aimed to provide association between glomerular filtration rate and body mass index among orthopaedic patients. A total of sixty (60) patients irrespective of gender were recruited. Weight and height were measured prior to the sample collection. A structured questionnaire was administered to obtain the demographic data of the subjects. Blood samples were collected from each patient by venepuncture from the antecubital vein of the forearm using disposable syringes. Serum creatinine was determined by method of Rosano et al. Body Mass Index and Glomerular Filtration Rate (eGFR) were calculated using creatinine-based equation of Modification of Diet in Renal Disease. Mean BMI was found to be higher in females (25.48±5.65) than their male counterparts (21.44±4.52), while eGFR was found to be higher in males (184.14±53.23) than in females (152.06±32.71). Subjects with eGFR ≥60 were observed to be more frequent (98.30%); normal weight individuals had higher frequency (48.33%). Positive correlation exists between BMI and eGFR in males whereas negative correlation was found in females which indicates association between body mass index and kidney function is gender related.